Differentiation of patented crystalline glucosamine sulfate from other glucosamine preparations will optimize osteoarthritis treatment - Sukit Saengnipanthkul (2019)
© 2017 Asia Pacific League of Associations for Rheumatology and John Wiley & Sons Australia, Ltd Symptomatic slow-acting drugs for osteoarthritis (SYSADOAs) are recommended for the medium- to long-term management of knee osteoarthritis (OA) due to their abilities to control pain, improve function and delay joint structural changes. Among SYSADOAs, evidence is greatest for the patented crystalline glucosamine sulfate (pCGS) formulation (Mylan). Glucosamine is widely available as glucosamine sulfate (GS) and glucosamine hydrochloride (GH) preparations that vary substantially in molecular form, pharmaceutical formulation and dose regimen. Only pCGS is given as a highly bioavailable once-daily dose (1500 mg), which consistently delivers the plasma levels of around 10 μmol/L required to inhibit interleukin-1-induced expression of genes involved in the pathophysiology of joint inflammation and tissue destruction. Careful consideration of the evidence base reveals that only pCGS reliably provides a moderate effect size on pain that is higher than paracetamol and equivalent to non-steroidal anti-inflammatory drugs (NSAIDs), while non-crystalline GS and GH fail to reach statistical significance for pain reduction. Chronic administration of pCGS has disease-modifying effects, with a reduction in need for total joint replacement lasting for 5 years after treatment cessation. Pharmacoeconomic studies of pCGS demonstrate long-term reduction in additional pain analgesia and NSAIDs, with a 50% reduction in costs of other OA medication and healthcare consultations. Consequently, pCGS is the logical choice, with demonstrated medium-term control of pain and lasting impact on disease progression. Physician and patient education on the differentiation of pCGS from other glucosamine formulations will help to improve treatment selection, increase treatment adherence, and optimize clinical benefit in OA.